2020
DOI: 10.30766/2072-9081.2020.21.5.521-530
|View full text |Cite
|
Sign up to set email alerts
|

Influence of weather conditions on the duration of the growth season and yield of peas

Abstract: During the period from 2012 to 2019 in the conditions of the Kirov region there were some studies aimed at investigating the influence of hydrothermal factors (temperature, precipitation) on the duration of pea growth season, yield and constituent elements of yield productivity. The study objects were 3 pea varieties of different morphotypes bred by the Falenki Breeding Station (Falenskiy yubileynyy, Ryabchik, Falenskiy usatyy). The weather conditions during the research were contrasting in temperature regime … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…At the same time, it is also noted that the current temperature regime in the region harms pea productivity. It is noteworthy that a similar influence of climatic factors was noted in other regions of Russia [43]. In the conditions of the Ural region (Republic of Bashkortostan), Kuznetsov et al [6] found that the highest yield of field peas was observed in years when the temperature during the growing season was 0.81-1.10.…”
Section: Discussionmentioning
confidence: 56%
“…At the same time, it is also noted that the current temperature regime in the region harms pea productivity. It is noteworthy that a similar influence of climatic factors was noted in other regions of Russia [43]. In the conditions of the Ural region (Republic of Bashkortostan), Kuznetsov et al [6] found that the highest yield of field peas was observed in years when the temperature during the growing season was 0.81-1.10.…”
Section: Discussionmentioning
confidence: 56%